2017
DOI: 10.1136/jramc-2016-000725
|View full text |Cite
|
Sign up to set email alerts
|

Support needs and experiences of family members of wounded, injured or sick UK service personnel

Abstract: The findings of this study suggest that family members of WIS personnel value proactive, direct and sustained communication from support service providers. We suggest that families of UK service personnel may benefit from family care coordinators, who could provide continuous and consistent care to family members of WIS personnel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Such findings may be due to the increased challenges posed by psychological J o u r n a l P r e -p r o o f injuries, 27 greater distress among the partners of military personnel and veterans with mental health problems, and a competing desire to protect personnel and veterans from being identified as having difficulties. 47 Associations between psychological distress, partner caregiver burden and considerations of divorce and partner perceptions of personnel or veteran psychological injury may also be important. 39 These findings were consistent with previous civilian research suggesting a lower emotional burden among family caregivers of individuals with physical disabilities and injuries compared to family caregivers of those with psychological disorders 48; 49 and suggest CRPIs do pose different challenges for the partners of military personnel and veterans but more research is needed to understand how and why.…”
Section: Discussionmentioning
confidence: 99%
“…Such findings may be due to the increased challenges posed by psychological J o u r n a l P r e -p r o o f injuries, 27 greater distress among the partners of military personnel and veterans with mental health problems, and a competing desire to protect personnel and veterans from being identified as having difficulties. 47 Associations between psychological distress, partner caregiver burden and considerations of divorce and partner perceptions of personnel or veteran psychological injury may also be important. 39 These findings were consistent with previous civilian research suggesting a lower emotional burden among family caregivers of individuals with physical disabilities and injuries compared to family caregivers of those with psychological disorders 48; 49 and suggest CRPIs do pose different challenges for the partners of military personnel and veterans but more research is needed to understand how and why.…”
Section: Discussionmentioning
confidence: 99%
“…In the UK there is a paucity of research exploring military partners’ experiences of stigma and rarely do discussions draw connections to normative power (critical approaches are discussed in the next section). Yet, it has been indicated that partners might avoid support-seeking because they do not want to be labelled a ‘welfare case’, are worried about potential negative impacts on their service partner’s career, and the wider stigmatisation associated with mental health and domestic abuse (Verey et al, 2017; Walker et al, 2020; Williamson, 2012). Furthermore, stigma might be exacerbated by partners not trusting the training and confidentiality of military-organised providers, concerns about privacy in close-knit communities, and concerns about being judged by other partners assuming rank (Dandeker et al, 2006; Long, 2019; Williamson, 2012).…”
Section: Stigma Support-seeking and ‘Gazing Up’mentioning
confidence: 99%